2019
DOI: 10.1111/nicc.12412
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses' self‐assessed patient observation skills: a cross‐sectional survey study

Abstract: Background Observing a patient's clinical condition is an important responsibility of critical care nurses and an essential component of their competence. Critical care nurses' patient observation skills contribute to patient safety and quality of care. These observation skills have not been assessed or measured previously. Aim The aim of this study was to measure the self‐assessed level of critical care nurses' patient observation skills and to explore the factors associated with these skills. Study design Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Confidence in: (a) recognizing core symptoms of dementia, (b) assessing core symptoms of dementia, (c) communicating effectively with people with dementia, (d) providing psycho-education to people with dementia, (e) activating people with dementia mentally, (f) activating people with dementia physically, (g) managing behavioral symptoms, (g) managing psychological symptoms, and (h) involving careers in the treatment of people with dementia were assessed pre- and post-intervention. The psychometric properties of these VAS were not investigated in the present study, although it has been used in prior training interventions to assess confidence in specific, medical skills [ 19 , 20 ]. Prior research demonstrated as well that VAS are valid in assessing confidence for specific medical skills [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Confidence in: (a) recognizing core symptoms of dementia, (b) assessing core symptoms of dementia, (c) communicating effectively with people with dementia, (d) providing psycho-education to people with dementia, (e) activating people with dementia mentally, (f) activating people with dementia physically, (g) managing behavioral symptoms, (g) managing psychological symptoms, and (h) involving careers in the treatment of people with dementia were assessed pre- and post-intervention. The psychometric properties of these VAS were not investigated in the present study, although it has been used in prior training interventions to assess confidence in specific, medical skills [ 19 , 20 ]. Prior research demonstrated as well that VAS are valid in assessing confidence for specific medical skills [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alastalo et al . () used a paper‐and‐pencil questionnaire to assess nurses' competence in patient observations. The nurses self‐assessed their competence.…”
mentioning
confidence: 99%